2018
DOI: 10.1080/13625187.2018.1455179
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in young women starting hormonal contraception: a pilot study

Abstract: Objectives: Our purpose was to study whether there is a difference in self-rated health-related quality of life (HRQOL) and changes in HRQOL perception after 3 months of hormonal contraceptive use in adolescents. Seasonal variations in symptoms of depression were also studied. Methods: A test group (T1) (n ¼ 193) and a selected control group (n ¼ 238) of women aged 14-20 years who were visiting a young person's clinic completed the 36-item short-form health survey (SF-36) and answered additional questions on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…In this study, Majority of the studied group (92.6%) had dysmenorrhea. This coincides with Grandi et al (7) who found that 57.9% of their studied cases had dysmenorrhea Regarding the menstrual pain severity, it was mild to moderate in half of the women (52%), which is near to the results in the study done by Kristjánsdóttir et al (5) who studied 431 female on oral contraceptive pills and found that 35.3% of the studied cases had regular menstrual pain.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, Majority of the studied group (92.6%) had dysmenorrhea. This coincides with Grandi et al (7) who found that 57.9% of their studied cases had dysmenorrhea Regarding the menstrual pain severity, it was mild to moderate in half of the women (52%), which is near to the results in the study done by Kristjánsdóttir et al (5) who studied 431 female on oral contraceptive pills and found that 35.3% of the studied cases had regular menstrual pain.…”
Section: Discussionsupporting
confidence: 88%
“…In the study done by Grandi et al (7) , in Italy who studied 40 patients, the mean age at menarche was 12.84 ± 1.95 y. In a study done in Sweden, by Kristjánsdóttir et al (5) , the mean age of menarche was 12.9 ± 1.3 y.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar results were reported from a small, cross-sectional Norwegian study in adult women showing a decreased likelihood of a current mood disorder in users of combined contraceptive preparations, whereas, in contrast, users of progestin-only agents experienced a deleterious effect [ 9 ]. One small study in women aged 14–20 years found no significant changes in self-rated quality of life perception or depressive symptoms, despite the fact that both the number of days of menstrual bleeding and the use of analgetic medication to relieve menstrual pain were both reduced [ 10 ]. In a double-blind, randomized, placebo-controlled trial in 340 young, healthy Swedish women aged 18–35 years, Zethraeus et al demonstrated that a first-choice levonorgestrel-containing drug administered for the treatment of premenstrual symptoms resulted in a statistically significant reduction in general well-being, when compared to a placebo, but no statistically significant effects on depressive symptoms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%